Camp Cookery. How to Live in Camp - Parloa, Maria, 1843-1909 (Salt Lake City, UT : Project Gutenberg, 2017)
"Camp Cookery. How to Live in Camp" by Maria Parloa is a practical guidebook written in the late 19th century, specifically aimed at those interested in camping and outdoor cooking. It offers insights into how to efficiently set up a campsite, select appropriate equipment, and prepare various meals while living in a camp setting. The book caters to outdoor enthusiasts and provides extensive tips on provisions and cooking methods suited to the wilderness lifestyle. The content of the book is organized around essential aspects of camp life, including the selection of suitable camping equipment, such as tents and stoves, and practical advice on cooking various foods like birds, fish, meats, and vegetables. Parloa emphasizes cleanliness, organization, and the importance of using the right utensils to aid in cooking. Each chapter features recipes that are straightforward and easy to follow, ensuring readers can replicate the dishes with limited resources. With an emphasis on maintaining comfort and hygiene in a camping environment, the book serves as a comprehensive resource for anyone seeking to enhance their outdoor culinary skills. (This is an automatically generated summary.)
Release date is 2017-02-08
E-text prepared by Emmy, MFR, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Cooking, American; Camping